Pre-treatments of Lithium Foil Surface for Improving the Cycling Life of Li Metal Batteries - Delaporte, Nicolas; Wang, Yuesheng; Zaghib, Karim (Frontiers in Materials, 2019)
Liquid electrolytes used in Li-ion batteries are flammable and slowly degrade to form a solid electrolyte interface (SEI) that irreversibly consumes lithium, decreasing the Coulombic efficiency of the battery. In addition, lithium anodes undergo severe morphology changes during cycling and Li dendrites are formed, which may cause short-circuits inside the battery. Safety concerns and the requirement of higher energy density have stimulated a search for a durable solid-state lithium rechargeable battery (SSLB) with an inorganic or dry polymer electrolyte that is more stable toward the lithium metal and suppresses the growth of lithium dendrites. Reducing the reactivity and increasing the poor contact between solid interfaces in these all-solid-state batteries remain challenging and Li-surface modification is one option to be explored to remedy these problems. Here, we review recent progress in surface pre-treatment of 2D lithium foil to enhance the electrochemical performance of various battery configurations. The review is organized based on the different types of modification reported in the literature.